The effect of gastric acid on the surface properties of different universal composites: A SEM study - Kedici Alp, Cemile; Gündoğdu, Ceyda; Dağdelen Ahısha, Cansu (Hindawi Limited, 2022)
The aim of this study is to compare surface roughness and microhardness changes of three monochromatic (Omnichroma, Vittra Unique, and Charisma Diamond One) and three universal shade (Neo Spectra ST, G-ænial A'CHORD, and Nova Compo C) resin composites after exposure to simulated gastric acid. A total of 144 disc-shaped specimens (24 discs of each composite resin) were prepared using plexiglass molds (R=5 mm×h=2 mm) for evaluation from each material. Specimens of each material were divided into two main groups for the evaluation of the microhardness and surface roughness and also two subgroups for 7- and 14-day exposures to simulated gastric acid. Initial microhardness and surface roughness measurements of all samples were measured before immersion (T1) followed by exposing the samples to simulated gastric acid for 7 days (T2) and 14 days (T3), and then, the microhardness and roughness measurements were repeated. Randomly selected specimens of each material for each of the time intervals (T1, T2, and T3) were evaluated with scanning electron microscopy (SEM). One-way ANOVA revealed that the surface roughness and hardness values of all tested composite resin restorative materials show no statistically significant difference for the initial (T1) value (p>0.05). Regarding the 7th day (T2) and 14th day (T3) surface roughness and microhardness value of all composites, there are statistically significant differences between the groups (p[removed]0.05). As a result of this in vitro study, increase in surface roughness and decrease in microhardness of the tested universal composite materials when exposed to simulated gastric acid were statistically significant.
Keywords: Different Universal Composites; Gastric Acid; Surface Properties